Linear multi-photon storage based on dark modes with frequency tuning - Shuang Xu; Wei-Jiang Gong; H Z Shen; X X Yi (New Journal of Physics, 2021)
We propose a quantum memory applicable to the optical regime based on a linear system. The system is in a symmetrical star configuration: one central mode is both connected to the input–output channel and uniformly coupled to a number of modes with tunable frequencies. We show that, as long as the number of these tunable modes is double an odd number, such a configuration is just flexible enough to perform the storage and on-demand recall of a number of individual photons. Tuning of the mode frequencies is feasible experimentally by means of adiabatic frequency tuning, and we show the system is scalable and robust against various type of imperfections. Moreover, the linearity of the system is compatible with the use of single-mode continuous-variable error correction code. Our results therefore provide a promising approach to the storage of many photons carrying protected quantum information.